(3OjhGf GHf GdQhejs - (3Ydj Hf GdYHGS Hf LQjL, Ch LhQLjS, GdQhej, CHh GdMSf,J (B283 (3g` s ((3YHOGdQMef Hf CMeO Hf YHGS s)
(3ChdgG (B:s
(3bGd jeOM(B: (3CjgG GdbGSe GdbSje QhGA hGdPj Ve hOg GdCghGA s
(3BNQgG (B:s
(3CfJ YhOJfj GdJSMH HGdMd` e, adG JefYfj JYhjOc s
(3hQOJ JMJ Qbe (B2191s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B114s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B109 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B766s
Keywords: (3GdCOHs